Past and current evidence of persecution of the Endangered crowned eagle Harpyhaliaetus coronatus in Argentina - Sarasola, José Hernán (2006)
The crowned eagle Harpyhaliaetus coronatus is a large Neotropical eagle categorized as Endangered throughout its range. However, the threats to this species are poorly understood. We present data on the causes of death of crowned eagles in semi-arid forests of La Pampa province, central Argentina. Data was obtained from field surveys and from interviews with 62 local landowners during 1999–2004. Over this period five eagles were shot, one killed by a car, one was found dead in a cattle water trough, and one was found in captivity. From the interviews information was obtained about a further 10 cases of eagles being shot, disturbed or trapped. Five (13%) of 38 interviewed landowners who positively identified the species admitted having killed or disturbed eagles in the past but only two (5%) mentioned predation of eagles upon livestock as a problem. Persecution seems to be a significant threat to this species in central Argentina and future research and conservation action should be focused not only on gaining a better knowledge of the biology of the species but also on conservation and educational programmes involving local people. a large Neotropical eagle categorized as Endangered throughout its range. However, the threats to this species are poorly understood. We present data on the causes of death of crowned eagles in semi-arid forests of La Pampa province, central Argentina. Data was obtained from field surveys and from interviews with 62 local landowners during 1999–2004. Over this period five eagles were shot, one killed by a car, one was found dead in a cattle water trough, and one was found in captivity. From the interviews information was obtained about a further 10 cases of eagles being shot, disturbed or trapped. Five (13%) of 38 interviewed landowners who positively identified the species admitted having killed or disturbed eagles in the past but only two (5%) mentioned predation of eagles upon livestock as a problem. Persecution seems to be a significant threat to this species in central Argentina and future research and conservation action should be focused not only on gaining a better knowledge of the biology of the species but also on conservation and educational programmes involving local people. a large Neotropical eagle categorized as Endangered throughout its range. However, the threats to this species are poorly understood. We present data on the causes of death of crowned eagles in semi-arid forests of La Pampa province, central Argentina. Data was obtained from field surveys and from interviews with 62 local landowners during 1999–2004. Over this period five eagles were shot, one killed by a car, one was found dead in a cattle water trough, and one was found in captivity. From the interviews information was obtained about a further 10 cases of eagles being shot, disturbed or trapped. Five (13%) of 38 interviewed landowners who positively identified the species admitted having killed or disturbed eagles in the past but only two (5%) mentioned predation of eagles upon livestock as a problem. Persecution seems to be a significant threat to this species in central Argentina and future research and conservation action should be focused not only on gaining a better knowledge of the biology of the species but also on conservation and educational programmes involving local people. Harpyhaliaetus coronatus is a large Neotropical eagle categorized as Endangered throughout its range. However, the threats to this species are poorly understood. We present data on the causes of death of crowned eagles in semi-arid forests of La Pampa province, central Argentina. Data was obtained from field surveys and from interviews with 62 local landowners during 1999–2004. Over this period five eagles were shot, one killed by a car, one was found dead in a cattle water trough, and one was found in captivity. From the interviews information was obtained about a further 10 cases of eagles being shot, disturbed or trapped. Five (13%) of 38 interviewed landowners who positively identified the species admitted having killed or disturbed eagles in the past but only two (5%) mentioned predation of eagles upon livestock as a problem. Persecution seems to be a significant threat to this species in central Argentina and future research and conservation action should be focused not only on gaining a better knowledge of the biology of the species but also on conservation and educational programmes involving local people.